A Quality Improvement Project to Improve the Use of Mother's Own Milk (MOM) With Precision Oropharyngeal Therapy. (April 2020) - Wetzel, Christine M.; Davis, Lisa; Grohler, Nikki; Oprondek, David; Ruff, Debra; Lowery, Kaci; Heuer, Jessica; Mullvain, Maddi; Wolff, Jessica
Abstract : Background: Bioprotective properties of mother's own milk (MOM) support the use of targeted MOM administration methods, including oropharyngeal therapy (OPT) with MOM, which may mimic the protective effects of swallowed amniotic fluid, thereby improving infant health outcomes. Purpose: To increase the use of MOM-OPT in premature infants in the first week of life. Methods: Quality improvement methods were used to implement precision dosing of OPT. Results: After changing processes and replacing the colostrum immune therapy practice with longer-term precision OPT, the percentage of ordered doses administered to infants in the first week of life increased from 24% to 64%. There was also a 15% increase in very low birth-weight infants who received MOM (from 50% to 65%) at discharge. There were no reported adverse events related to OPT administration. Implications for Practice: Replacing the unit's short-term colostrum immune therapy protocol with the longer-term precision OPT increased the number of doses given in the first week of life and increased the number of very low birth-weight infants discharged receiving MOM. Implications for Research: Researchers should consider studying the reported positive effects of OPT related to infant response (positive oral stimulation, reduction in oral aversion, and improved oral feeding skills), parent participation in care, and maternal milk expression behaviors (longer milk expression duration).